An Experiment of Ant Algorithms : Case Study of Kota Kinabalu Central Town - Nor Rafidah, Mohamad (2005)
Shortest path is one of the optimization problems that are difficult to solve. There are many algorithms that used to solve this problem. In this study, ant algorithms are used to find the shortest path using a real data. Kota Kinabalu Central Town (KKCT) is been used as the real data, where the nodes represent as buildings, the arc represent as roads and weight on the arc represent as distance. The objectives of this study are to explore and evaluate the Ant System (AS) algorithm and Ant Colony System (ACS) algorithm in finding shortest paths. Both algorithms are compared. Simulation is used as a method in this study. This is because a simulator is been designed. There are several experiment carry out using the simulator. The experiments involved manipulating several parameters. As a result, the AS was found to be not suitable for the real data used because KKCT is a graph without Hamiltonian cycle. ACS was found to be suitable for KKCT real data and produced an optimal solution.